Bringing the Hands to Mind: Embodied Attention in Chinese Buddhist and Latin Christian Hand Mnemonics - Lucas, Hannah (Numen, 2026)
This article examines hand mnemonics as technologies of ritual practice in the medieval world, comparing an unstudied tenth-century Chinese Buddhist mnemonic from Dunhuang (Bibliothèque nationale de France MS Pelliot Chinois 3835) with Latin Christian "meditation hands" from thirteenth- to fifteenth-century Europe. Through phenomenological analysis of their attentional protocols - or how they "bring the hands to mind" - the article identifies cross-cultural patterns and divergences between the mnemonics. Where the Latin hands promise an internal, therapeutic transformation through contemplative self-examination, the P.3835 example serves a primarily apotropaic function via protective spells against external threats. Nevertheless, embodied attention provides a phenomenological link between these traditions, as well as between the P.3835 mnemonic and other texts in its manuscript miscellany, revealing the hybridity of "Buddho-Daoist" ritual practices at Dunhuang. By the article’s conclusion, the hand emerges as a complex nexus where ritual practitioner and world intersect, mediated through the simulacrum of the material text.